In Situ Plasma‐Grown Silicon‐Oxide for Polysilicon Passivating Contacts. Issue 21 (28th July 2020) - Alzahrani, Areej; Allen, Thomas G.; De Bastiani, Michele; Van Kerschaver, Emmanuel; Harrison, George T.; Liu, Wenzhu; De Wolf, Stefaan
Abstract: Large‐scale manufacturing of polysilicon‐based passivating contacts for high‐efficiency crystalline silicon (c‐Si) solar cells demands simple fabrication of thermally stable SiO x films with well controlled microstructure and nanoscale thickness to enable quantum‐mechanical tunneling. Here, plasma‐dissociated CO2 is investigated to grow in situ thin (<2 nm) SiO x films on c‐Si wafers as tunnel‐oxides for plasma‐deposited, hole‐collecting (i.e., p‐type) polysilicon contacts. It is found that such plasma processing offers excellent thickness control and superior structural integrity upon thermal annealing at 1000 °C, compared to state‐of‐the‐art wet‐chemical oxides. As a result, p‐type polysilicon contacts are achieved on n‐type c‐Si wafers that combine excellent surface passivation, resulting in an implied open‐circuit voltage exceeding 700 mV, with a contact resistance as low as 0.02 Ω cm 2 . Abstract : This article deals with the fabrication of a new hole‐selective, passivating contact for silicon solar cells. The introduced contact, which leads to much less surface recombination while being resilient to high processing temperatures, is fabricated in simple and elegant way, where all contact‐stack layers are deposited in the same plasma‐deposition chamber.